0040 Elevated 24-hour Free Fatty Acids During Circadian Misalignment. (27th April 2018) - Broussard, J L; Morton, S J; McHill, A W; Higgins, J; Melanson, E K; Wright, K P
Abstract: Introduction: Circadian misalignment— sleeping during the biological day and eating at a time when the internal circadian clock promotes sleep—is a risk factor for obesity and diabetes. However, little is known about mechanisms by which circadian misalignment leads to metabolic dysregulation in humans. Increased free fatty acids (FFA) can induce insulin resistance and are elevated during insufficient sleep. However, the impact of circadian misalignment on FFA has not been elucidated. We therefore examined circulating FFA, glucose and insulin during an inpatient simulated night shiftwork protocol. Methods: 14 healthy adults (6M; aged 26.4 ± 1.2y, BMI 22.7 ± 0.5 kg/m 2 ; mean±SD) participated in the study. Blood was sampled every 2 hours for 24 hours during circadian alignment and circadian misalignment and every 30 minutes after each meal for 2 hours. Blood was assayed for FFA, insulin and glucose. Participants were provided with a 3-day energy balance diet prior to study admission and the diet was continued inpatient. Diet was designed with the same meals each day. Results: Circadian misalignment was induced by our simulated nightshift work protocol, as evidenced by the melatonin rhythm which did not adapt to the nightshift schedule. Mean FFA levels were significantly elevated during wake (+41 ± 18%, p<0.05; results are mean±SEM), sleep (+35 ± 10%, p<0.01) and across 24h (+35 ± 15%, p<0.01) during circadian misalignment. Furthermore, we found elevations in 24h mean glucose (+7 ± 3%, p<0.05) and mean glucose in response to breakfast (+24 ± 6%, p<0.01) during circadian misalignment as compared to baseline, without a compensatory increase in insulin. Conclusion: Acute circadian misalignment results in elevated 24h FFA and glucose concentrations, as well as an increased glucose in response to the first meal of the day. Sustained chronically, these disturbances may increase the risk for developing type 2 diabetes. Support (If Any): This work was supported by an SRS CDA, K01DK110138, F32DK111161, R01HL132150, R21DK092624, and Society in Science, The Branco Weiss Fellowship, administered by the ETH Zürich.